2010
DOI: 10.1111/j.1365-3091.2010.01188.x
|View full text |Cite
|
Sign up to set email alerts
|

Turbiditic, clay‐rich event beds in fjord‐marine deposits caused by landslides in emerging clay deposits palaeoenvironmental interpretation and role for submarine mass‐wasting

Abstract: Distinct, clay-rich beds are common in fjord-marine deposits in Trondheimsfjorden near the outlet of the Nidelva River. Their characteristic light-grey colour makes the beds easily distinguishable from the surrounding brownish, bioturbated, muddy fjord sediments. The clay-rich beds commonly display a clear stratification in clay, silt and very fine sand. The beds are interpreted as originating primarily from large quick-clay landslides upstream along the Nidelva River. Such events resulted in a sudden increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
3
7
0
Order By: Relevance
“…A prerequisite for the occurrence of the weak event beds, such as those found in this study, is the presence of prehistoric clay-slide activity in the catchment and a low to moderately dipping fjord margin on which the event beds are able to accumulate (Hansen et al 2011). As sensitive, glacio-marine sediments and clay-slides are in Alaska, beds with a similar origin as to those found in this study could play an et al 199 ).…”
Section: Discussionsupporting
confidence: 70%
“…A prerequisite for the occurrence of the weak event beds, such as those found in this study, is the presence of prehistoric clay-slide activity in the catchment and a low to moderately dipping fjord margin on which the event beds are able to accumulate (Hansen et al 2011). As sensitive, glacio-marine sediments and clay-slides are in Alaska, beds with a similar origin as to those found in this study could play an et al 199 ).…”
Section: Discussionsupporting
confidence: 70%
“…Similar beds observed in other fjords around Norway (L’Heureux et al , ; Hansen et al ) and Canada (St‐Onge et al ) were identified as being the result of terrestrial quick‐clay landslides in the catchment of the fjord. Such events can produce a turbitdity current that propagates downstream into the fjord, rapidly draping the fjord bed.…”
Section: Discussionsupporting
confidence: 70%
“…The morphology and internal architecture of this event bed as imaged in the 3D seismic volume is consistent with this hypothesis. In particular, the manner in which the lower clay‐rich layer demonstrates limited run‐up on the foreshore slope and thickens south‐west, toward the Røssåga River, agrees with the fine‐grained, clay‐rich gravity flow that is expected to form the first deposit in such an event (Hansen et al ). The sandy interval may be associated with failure of the delta slope and/or flooding of the river (i.e., dam breach) following clay slide activity in the uplifted valley (L’Heureux et al ).…”
Section: Discussionsupporting
confidence: 69%
“…Fjords are unique archives of climatic and environmental changes, but also of natural hazards (e.g., [Syvitski et al, 1987] and [Syvitski and Shaw, 1995]; see also Howe et al, 2010 for a recent compilation of papers). They can preserve thin sediment sequences deposited under very high sediment accumulation rates, making them ideally suited to record historical and pre-historical sedimentological events such as major landslides (e.g., [L'Heureux et al, 2009] and [Hansen et al, 2011]), floods (e.g., [Bornhold et al, 1994], [Urgeles et al, 2002] and [Mulder and Chapron, 2010]) or earthquakes (e.g., [Blais-Stevens and Clague, 2001], [St-Onge et al, 2004], [Chapron et al, 2006], [Dallimore et al, 2008] and [Sepulveda et al, 2010]). These types of events may trigger the deposition of rapidly deposited layers (RDL) 1 with specific characteristics and geometries.…”
Section: Introductionmentioning
confidence: 99%